Study on the Construction of College English Teaching and Research Team in Military Academies: A Case Study of College English Team of Rocket Force University of Engineering - Liang, Ye; Zhang, Yuxuan; Wang, Yin (Transactions on Economics, Business and Management Research, 2023)
The construction of college English team in military academies is mostly based on their own training programs and curriculum systems, which optimize the teaching structure, but have little effect in promoting the collaborative development of individuals and teams, and can’t satisfy the actual needs of teaching and scientific research innovation. Based on the full investigation of the needs of college English team construction in military academies, this study promotes the overall improvement of individual and team teaching and research levels through three paths: reorganizing the team structure, setting up the team operation mechanism, and building the team culture, so as to achieve the mutual promotion between teaching and research.